Debunking Health IT Usability Myths - Staggers, N.; Xiao, Y.; Chapman, L. (Applied Clinical Informatics, 2013)
Poor usability is a threat to patient safety and linked to productivity loss, workflow disruption, user frustration, sub-optimal product use and system de-installations. Although usability is receiving more attention nationally and internationally, myths about usability persist. This editorial debunks five common myths about usability (1) usability only concerns the look and feel of a product and is, therefore, only a minor concern, (2) usability is not measurable, (3) usability stifles innovation, (4) vendors are solely responsible for product usability, and (5) usability methods are not practical for use in healthcare.
Keywords: Usability; user experience; human-computer interaction